2020
DOI: 10.1159/000505691
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Scaffold with Human Umbilical Cord Mesenchymal Stem Cells Remarkably Improves Intrauterine Adhesions in a Rat Model

Abstract: Background: Intrauterine adhesion (IUA) is the second leading cause of secondary infertility in women. Research has shown that stem cells can promote endometrial regeneration and that biomaterials are also helpful in tissue regeneration. Therefore, we compared the efficacy of a collagen scaffold combined with either human umbilical cord mesenchymal stem cells (hUCMSC) or estrogen for the treatment of IUA. Methods: The IUA-induced rats were injected with hUCMSCs or estrogen, and with a collagen scaffold. The en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…These strategies afforded limited effects in alleviating endometrial fibrosis and inhibiting adhesion reformation, especially in severe IUA. Therefore, intrauterine injection of hyaluronic acid colloids, amniotic membrane transplantation, and stem cell therapy have been employed [ 71 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. Treatment with human umbilical cord mesenchymal stem cell-extracellular vesicles (UCMSC-EVs) alone or combined with estrogen significantly decreased not only inflammatory cytokines, such as TNF-α and IL-6, but also fibrosis markers, such as TGF-β, COL1α1, and VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…These strategies afforded limited effects in alleviating endometrial fibrosis and inhibiting adhesion reformation, especially in severe IUA. Therefore, intrauterine injection of hyaluronic acid colloids, amniotic membrane transplantation, and stem cell therapy have been employed [ 71 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. Treatment with human umbilical cord mesenchymal stem cell-extracellular vesicles (UCMSC-EVs) alone or combined with estrogen significantly decreased not only inflammatory cytokines, such as TNF-α and IL-6, but also fibrosis markers, such as TGF-β, COL1α1, and VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed that transplantation of bone marrow-derived stem cells, hematopoietic stem/progenitor cells, endometrial MSCs, embryonic stem cells, amniotic MSCs, and blood-derived stem cells can effectively promote the endometrial regeneration and menstrual recovery of IUA animal models or patients [84][85][86]. To improve the endometrial receptivity and improve the therapeutic effect of stem cell transplantation, Zhang et al [87] combined platelet-rich plasma (PRP) and blood-derived stromal cells in the IUA rat model in order to explore the therapeutic mechanisms.…”
Section: Research Progress and Limitationsmentioning
confidence: 99%
“…MSCs secrete a variety of cytokines (e.g., VEGF-A, TGF-β1, FGF-2) to promote glandular and vascular growth and degradation of fibrous scars (Ding et al, 2014;Xin et al, 2019;. Collagen increases the number of endometrial glands and endometrial thickness, reduces the area of fibrosis and improves pregnancy rates in a rat model (Ding et al, 2014;Liu et al, 2020). Compared with collagen alone, combining hUCMSCs more significantly increased the number of glands and reduced the area of fibrosis (Liu et al, 2020), and combining BMSCs was more effective in improving pregnancy rates, as well as in myometrium recovery and revascularization (Ding et al, 2014).…”
Section: The Application Of Hydrogels Combined With Mscs In Iuamentioning
confidence: 99%